Transformaciones y aspectos socioculturales presentes en el Programa de Restaurantes Escolares de Medellín desde 1961 a 2010 (2016)
ABSTRACT: Diet is a complex sociocultural act providing biological, nutritional, political and social dimensions. Interlocking them creates inequalities such as food shortages and access to food through social programs. The aim of this study is to identify the changes in the program of school restaurants in Medellin (Colombia), and to interpret the perception of the program’s beneficiaries. Material and Methods: Qualitative and historical perspectives; ethnography and history of the present time. Ethnography was conducted with school beneficiaries and their parents, councilors, program coordinators, food handlers and nutritionists. Historical Archives of Medellin and Minutes Archive Medellin Municipal Council were reviewed to collect the historical information, reports and correspondence. Results: The program has different models of service provision and different coverage; it has retained the sympathy of the mayors and officials of the various secretariats. This was set up at the beginning, in 1935, from a perspective of charity school by elite women, and then it had a hygienist and nutritional vision of right to food; and finally, a food and nutrition safety vision. In the supplied speeches and preparations, the absence of cultural references is identified. Conclusions: School Restaurants programs help to reduce the suffering caused by hunger, but they are not always designed thinking about the cultural aspects that involves food.